Penguatan Kelembagaan TPQ di Kecamatan Tembarak, Kabupaten Temanggung - Muh Baehaqi; Eko Sariyekti (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2020)
Creating an institution (TPQ) running with good administrative and managerial patterns is not easy. Community service activities regarding institutional strengthening of the TPQ are expected to be able to improve the quality of the TPQ in the Tembarak Subdistrict of Temanggung Regency, particularly administrative, managerial, and TPQ’s emis data. Implementation of TPQ institutional strengthening activities in the form of FGDs, training, assistance, monitoring and evaluation, and exposure to results. The TPQ institutional strengthening target is that TPQ participants are increasingly opening their insights and knowledge related to TPQ administration, managerial, and emis data. In addition, this training was also able to increase the desire of TPQ teachers to be more orderly in administration. Ideally, a TPQ is a TPQ that has management in the field of management, thefield of administration, the field of teaching and learning activities, the field of finance, and the field of extracurricular good and right. Assistance from this activity was carried out with the practice of filling in the EMIS data directly, by presenting JFU for data filling from the Ministry of Religion in Temanggung Regency. The practice of TPQ emis data filling is able to provide encouragement and motivation so that TPQ teachers can fill their emis data independently after successfully activating TPQ.